การพัฒนาความสามารถในการอ่านโดยจัดการเรียนรู้แบบบูรณาการประสาทสัมผัสร่วมกับหลักการสอนแบบ 3Rs ของนักเรียนที่มีความบกพร่องทางสติปัญญา - เกษณี, สาวิตรี; ใจงาม, ศิริวิมล; จิตต์การุญ, ผ่องลักษม์ (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2017)
บทคัดย่อ การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อ 1) เพื่อศึกษาระดับความสามารถในการอ่านของนักเรียนที่มีความบกพร่องทางสติปัญญาหลังการจัดการเรียนรู้แบบบูรณาการประสาทสัมผัสร่วมกับหลักการสอนแบบ 3Rs 2) เพื่อศึกษาความก้าวหน้าในการอ่านของนักเรียนที่มีความบกพร่องทางสติปัญญาก่อนและหลังการจัดการเรียนรู้แบบบูรณาการประสาทสัมผัสร่วมกับหลักการสอนแบบ 3Rs กลุ่มตัวอย่างเป็นนักเรียนชั้นประถมศึกษา ปีที่ 2 ปีการศึกษา 2558 โรงเรียนบ้านห้วยไคร้ จำนวน 3 คน เครื่องมือที่ใช้ในวิจัยประกอบด้วย แผนการจัดการเรียนรู้ 3 หน่วย ได้แก่ หน่วยที่ 1 การอ่านพยัญชนะอักษรกลาง หน่วยที่ 2 การอ่านสระเดี่ยว หน่วยที่ 3 การอ่านคำประสม และแบบทดสอบการอ่าน วัดความสามารถในการอ่านวิเคราะห์ข้อมูลโดยใช้ค่าเฉลี่ย ร้อยละ และค่าดัชนีประสิทธิผล ผลการวิจัยพบว่า 1. ความสามารถในการอ่านของนักเรียนที่มีความบกพร่องทางสติปัญญาหลังการจัดการเรียนรู้แบบบูรณาการประสาทสัมผัสร่วมกับหลักการสอนแบบ 3Rs อยู่ในระดับดี 1 คน และระดับดีมาก 2 คน 2. ดัชนีประสิทธิผลความสามารถในการอ่านของนักเรียนที่มีความบกพร่องทางสติปัญญาทั้ง 3 คน หลังการจัดการเรียนรู้แบบบูรณาการประสาทสัมผัสร่วมกับหลักการสอนแบบ 3Rs มีความก้าวหน้าในการอ่านทั้ง 3 หน่วย โดยมีค่าดัชนีประสิทธิผลมากกว่า 0.50 Abstract The purposes of this research were 1) to study the students’ ability in Promoting reading Abilities for children with intellectual disability after studying by sensory integrated and 3Rs Teaching principles learning, 2) to study effectiveness index the student’s ability level in promoting reading abilities for children with intellectual disability after studying by sensory integrated and 3Rs teaching principles learning. The samples were 3 students who were studying in grade 2 in academic year 2015 at Banhuaykrai School. The research instruments were 3 units promoting reading ability plans of which were unit 1 reading medium tone consonants, unit 2 reading single vowels, and unit 3 reading compound words, achievement tests on reading abilities. The data resulted from the experimentation were analyzed by using mean ( ), percentage (%) and effectiveness index. The research results were as follows: 1. students’ reading abilities with intellectual disabilities after learning integrated with sensory teaching 3Rs principles’ found that 2 students were at a very high level and one student was are high level. 2. The index of productive ability of students with cognitive impairment after all three children, integrated with learning management and in cooperation with the main sensory teaching of the 3Rs, they are had the purposes in reading in 3 units with more than 0.50 effectiveness index.